Evaluation of Antioxidant Status of Two Limoniastrum Species Growing Wild in Tunisian Salty Lands - Mohamed Debouba; Sami Zouari; Nacim Zouari (MDPI AG, 2013)
We aim to highlight the differential antioxidant status of Limoniastrum guyonianum and Limoniastrum monopetalum in relation to their respective chemical and location characteristics. Metabolite analysis revealed similar contents in phenolic, flavonoïds, sugars and chlorophyll in the two species' leaves. Higher amounts of proline (Pro), carotenoïds (Carot), sodium (Na) and potassium (K) were measured in L. monopetalum leaves relative to L. guyonianum ones. While the two Limoniastrum species have similar free radical DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, L. guyonianum showed more than two-fold higher ferrous ions chelating activity relative to L. monopetalum. However, highest reducing power activity was observed in L. monopetalum. Thiobarbituric acid-reactive substances (TBARS) determination indicated that L. monopetalum behave better lipid membrane integrity relative to L. guyonianum. These findings suggested that the lesser stressful state of L. monopetalum was related to higher metabolites accumulation and reducing capacity compared to L. guyonianum.